Patient-Related Risk Factors for Chemotherapy-Induced Nausea and Vomiting: A Systematic Review - Mosa, Abu Saleh Mohammad; Hossain, A. Mosharraf; Lavoie, Beau James; Yoo, Illhoi (Frontiers in Pharmacology, 2020)
Background: Studies have reported that patient-related factors significantly impact the risk of Chemotherapy-Induced Nausea and Vomiting (CINV). The objective of this study was to analyze those risk factors of CINV through a systematic literature review. Methods: We searched MEDLINE to identify articles that addressed patient-related risk factors of CINV through clinical studies. Results: A total of 49 articles were selected for this study. A total of 28 patient-related risk-factors that significantly impact the risk of CINV were documented. Three factors are demographically-related, 17 factors are intrinsic in nature and innate to patient’s physiology or influenced by physiology, and eight factors are extrinsic in nature. At least five studies identified seven risk factors with notable summary odds ratio: history of nausea/vomiting (odds ratio: 3.13, 95% CI 2.40 – 4.07, p<0.05), female sex (odds ratio: 2.79, 95% CI 2.26 – 3.44, p<0.05), expectancy of CINV (odds ratio: 2.61, 95%CI 1.69 – 4.02, p<0.05), younger age (odds ratio: 2.59, 95% CI 2.18 – 3.07, p<0.05), anxiety (odds ratio: 2.57, 95% CI 1.94 – 3.40, p<0.05), history of morning sickness (odds ratio: 1.97, 95% CI 1.46 – 2.65, p<0.05), and low alcohol intake (odds ratio: 1.94, 95% CI 1.68 – 2.24, p<0.05). Conclusions: Oncologists can use these factors prior to the initiation of a chemotherapy regimen to identify patients at risk for CINV, in order to focus on more comprehensive antiemetic treatment options for those high-risk patients. This may enable better outcomes and avoid complications.